PENGARUH KUALITAS SISTEM INFORMASI AKADEMIK (SIAKAD) DAN KUALITAS PELAYANAN AKADEMIK TERHADAP KEPUASAN MAHASISWA DI TANRI ABENG UNIVERSITY KAMPUS TANGERANG - Mamad Sobari; Temmy Setiawan; Heru Sudinta (MANTRA (Jurnal Manajemen Strategis), 2026)
The Influence of Academic Information System (SIAKAD) Quality and Academic Service Quality on Student Satisfaction at Tanri Abeng University's Tangerang Campus. This study aimed to examine the partial and simultaneous effects of SIAKAD quality and academic service quality on student satisfaction. Using a quantitative survey of 96 respondents, the results showed that both variables had positive and significant effects on student satisfaction.